2009
DOI: 10.1029/2009gc002407
|View full text |Cite
|
Sign up to set email alerts
|

A Si‐Cl geothermobarometer for the reaction zone of high‐temperature, basaltic‐hosted mid‐ocean ridge hydrothermal systems

Abstract: [1] The chemical composition of mid-ocean ridge hydrothermal vent fluids is thought to reflect conditions within a deep-seated reaction zone. Although temperature and pressure conditions within this region are key parameters that characterize the subseafloor hydrothermal regime and the cooling of mid-ocean ridges, they are poorly constrained. In this paper, we developed a model in which high-temperature, vapor-type (low-salinity) vent fluid silica (Si) and chlorine (Cl) concentrations can be used to define lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
51
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 41 publications
7
51
0
1
Order By: Relevance
“…1, green squares). Region 2 is broadly consistent with P-T conditions associated with basalt-hosted hydrothermal systems when impacted by subseafloor magmatic intrusions (Fontaine et al, 2009;Fornari et al, 2012;Pester et al, 2014).…”
Section: Methodssupporting
confidence: 55%
“…1, green squares). Region 2 is broadly consistent with P-T conditions associated with basalt-hosted hydrothermal systems when impacted by subseafloor magmatic intrusions (Fontaine et al, 2009;Fornari et al, 2012;Pester et al, 2014).…”
Section: Methodssupporting
confidence: 55%
“…Where available, these efforts can be aided by geophysical data, which provide constraints on maximum depth of circulation if an axial magma chamber (AMC) is observed. For example, Fontaine et al (2009) demonstrated good agreement between AMC depth and maximum corresponding hydrostatic pressures derived using Si-Cl systematics. Deep crustal fluids, when encountering the given heat source that ultimately drives hydrothermal circulation, routinely intersect the two-phase boundary (Bischoff and Rosenbauer, 1984).…”
Section: Introductionmentioning
confidence: 65%
“…Dash-dot line represents the specific two-phase boundary of seawater (3.2 wt% NaCl) where deviation from the critical curve (solid line) is observed and the star is the critical point of seawater (Bischoff and Rosenbauer, 1988). The box denoted "Si-Cl" represents the pressure-temperature range of reaction derived for Lucky Strike by Fontaine et al (2009) using previously reported data, assuming quartz saturation was achieved in/near the two-phase region. While the fluids may have phase separated at temperatures >$430°C, Fe/Mn have equilibrated at lower temperatures (350-385°C).…”
Section: Temperature and Pressure Controls On Subseafloor Phase Equilmentioning
confidence: 98%
“…The Fe/Mn temperatures can be used in conjunction with dissolved Si, Cl and geophysical data to constrain possible subseafloor reaction conditions in pressure-temperature space (Bischoff and Rosenbauer, 1985;Foustoukos and Seyfried, 2007c;Fontaine et al, 2009;Pester et al, 2011). The extent of chloride variability in Lucky Strike fluids is sufficiently small that phase separation is likely occurring at conditions that do not significantly deviate from the critical curve in the NaCl-H 2 O system.…”
Section: Temperature and Pressure Controls On Subseafloor Phase Equilmentioning
confidence: 99%
See 1 more Smart Citation